Peranan Suami Dalam Upaya Penanggulangan Kekurangan Energi Kronis (KEK) Ibu Hamil - Nani Ratnaningsih, Rizqie Auliana (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Since Indonesia suffered monetary crisis, the government program was Social Safeguard Net Program in the field of healthy for pregnant woman through Pemberian Makanan Tambahan Pemulihan (PMTP) program. Target of PMTP program is the chronic energy deficiency (CEO) of pregnant woman. The problem of PMTP program is not readiness of the family, which obtain PMTP program. However, pregnancy is not only woman responsibility, but also family responsibility especially the husband. Objective: The objective of research is to know the role of husband in order to overcome the CED of pregnant woman and to find some factors that affect the role of husband in order to overcome the CEO of pregnant woman. Methods: Research sample is the husband of pregnant woman, who suffered the CED in Puskesmas Salaman 1, Kecamatan Salaman, Kabupaten Magelang, Central Java. Research instrument is questionnaire to know knowledge, attitude, and action of the husband. Data collection method is to interview the husband and direct measurement of height, weight, and upper arm s circle of pregnant woman. Knowledge of husband is scored 1 (right) and 0 (wrong). Attitude of husband is scored 4 (very agree), 3 (agree), 2 (disagree) and 1 (very disagree). Action of husband is analyzed descriptively. Correlation and regression analysis with SPSS version 10 and SPS 2000 program are used to analysis data. Results and conclusion: The role of husband in order to overcome the CED of pregnant woman is shown by knowledge, attitude, and action. Knowledge of husband consist good knowledge 2.86%, intermediate knowledge 77.14% and bad knowledge 20.00%. Attitude of husband consist good attitude 97.14%, bad attitude 2.86% and intermediate attitude 0%. Actions of husband are example to deliver pregnancy checking; to care during pregnancy; to suggest consuming nutritious food; to control during eating; to suggest taking medicine; to follow PMTP program; to prepare baby needs; and to help home works. Age of marriage, education level and kind of work have significant correlation with the knowledge of husband. Age of husband, age of marriage, education level and kind of work have significant correlation with attitude of husband. Knowledge and attitude of husband have significant correlation. Education level, age of marriage, kind of work, age of husband, number of life child and number of birth give lower effective contribution toward the knowledge of husband. Education level, age of marriage, kind of work, number of life child, number of birth and age of husband give lower effective contribution toward the attitude of husband. Keywords: husband, chronic energy deficiency, pregnant woman